Human rights and the concept of a human community with a shared future - Chang, Jian 1957-; Wei, Zhang (Chinese Perspectives on Human Rights and Good Governance, 2021)
This volume presents the concept of a Human Community with a Shared Future as a new path towards the realization of human rights. This idea tries to encourage all countries and economies to focus on a shared future and common destiny for all humankind as well as to work together to build a Human Community with a Shared Future through interdependence and joint development. The present volume consists of a collection of texts arising from conferences organized by the China Society for Human Rights Studies. The texts centre on the concept of a Human Community with a Shared Future, reflecting the current reality and extent of human rights thinking with respect to both law and policy in establishment circles in China, and helping to demonstrate the likely direction of official policy in the near future